An Inside-out Review of Lexical Collocations: Considerations for Teaching and Learning Vocabulary in EFL Contexts - Ahmad, Zulfiqar (International Journal of Linguistics, Literature and Translation, 2019)
Assuming the importance of lexical competence as a crucial variable in learning English as a Foreign Language, this paper attempts to discuss lexical collocations including the phrasal verbs from theoretical and pedagogical point of view. More specifically, the paper focuses on how collocations and phrasal verbs are composed in terms of their lexico-grammar and semanticity. The study also reveals learners' problems with the form, meaning, use and phonology of collocations and phrasal verbs. The paper concludes with the mention of some practical teaching measures based on awareness-raising and practical tasks as a solution to these issues. It is anticipated that these will provide EFL teachers an insight into the concept and use of collocations and phrasal verbs to make their teaching practice more effective.